2001
DOI: 10.1046/j.1365-3156.2001.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the prevalence of Oesophagostomum bifurcum and Necator americanus infections using specific PCR amplification of DNA from faecal samples

Abstract: SummaryUntil recently infection of humans with Oesophagostomum bifurcum was regarded as a rare zoonosis. But in northern Togo and Ghana its prevalence is 50% or more in certain villages. Diagnosis is hampered by the fact that the eggs of O. bifurcum are morphologically identical to those of the hookworm Necator americanus. Stools have to be cultured for 7 days to allow eggs to hatch to the characteristic third-stage (L3) larvae. We evaluated the applicability of speci®c polymerase chain reactions (PCRs) to amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 18 publications
3
66
0
5
Order By: Relevance
“…was extracted using the QIAamp DNA Mini kit (Qiagen, Germany) according to the kit's protocol with slight modifications (Verweij et al, 2001). DNA extraction was performed just on stool samples which were positive with zinc chloride fl otation method.…”
Section: Dna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…was extracted using the QIAamp DNA Mini kit (Qiagen, Germany) according to the kit's protocol with slight modifications (Verweij et al, 2001). DNA extraction was performed just on stool samples which were positive with zinc chloride fl otation method.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Among different PCR methods, multiplex PCR is considered useful for the detection of taeniid eggs from both individual animals, as well as in epidemiological studies (Trachsel, et al, 2007). A previous study (Yamasaki et al, 2004) had successfully demonstrated a multiplex PCR assay for the differential diagnosis of taeniasis and cysticercosis in humans (Taenia saginata, T. asiatica, and T. solium). This technique is therefore very useful in the accurate identifi cation of Taeniid cestode eggs, and overcomes the limitations of identifi cation by morphology (Yamasaki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The DNA extraction for the specimens from LUMC was performed using regular QIAamp mini Kit spin columns with modifications, which included a pretreatment with PVPP (polyvinylpyrrolidone) and boiling. 12 Protozoa-positive controls were extracted using an automated nucleic acid isolation system, QuickGene-810, with QuickGene DNA tissue kit S (Fujifilm, Tokyo, Japan). The manufacturer's protocol was modified to accommodate a larger input stool volume of 200 mg.…”
Section: Control Materialmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Realtime PCR has proved to be highly sensitive and 100% specific in detecting S. stercoralis and hookworm infections as compared with microscopy. 9,15 Hence, real-time PCR of several helminth species provides a worthwhile diagnostic alternative because it allows multiplex detection and quantification while it decreases the chances of human error and DNA contamination as compared with conventional PCR.…”
Section: Introductionmentioning
confidence: 99%